THE EFFECT OF KATUK LEAF DECOCTION ON BREAST MILK PRODUCTION IN BREASTFEEDING MOTHERS - Erlin Ady Kurnia; Arsi, Ranida; Fitri Afdhal (LPPM STIKES Al-Ma'arif Baturaja, 2026)
The issue of inadequate breast milk (ASI) production among lactating mothers is a primary obstacle to the practice of exclusive breastfeeding for six months. “Insufficient breast milk production may stem from stress, exhaustion, inadequate nursing stimulation, or insufficient lactation-supportive nutrition. This study sought to assess the impact of katuk leaf (Sauropus androgynus) decoction on breast milk production in breastfeeding mothers residing in Kurungan Nyawa I Village, Buay Madang District, East OKU Regency. The intervention is providing 150 ml of Katuk leaf decoction everyday for seven consecutive days. This study employed a quasi-experimental design utilizing a pretest-posttest methodology without a control group. The sample comprised 17 lactating mothers. The Shapiro-Wilk test was employed to assess data normality, and the data were analyzed using the Paired Sample T-Test. The results indicated a substantial impact of Katuk leaf decoction on enhancing breast milk production, with a p-value of 0.000 (p<0.05). The mean breast milk volume prior to treatment was 76.47 ml, which rose to 122.12 ml post-intervention, reflecting an average increase of 45.53 ml. This notable enhancement indicates that katuk leaf decoction positively influences breast milk production. Breastfeeding women with insufficient milk supply are advised to take katuk leaf decoction as a natural remedy to enhance lactation.